Can Rural Tourism Satisfy Portuguese Tourist's Needs? Examining Portuguese Tourist's Preferences - Antunes, Joaquim (2017)
Tourism is considered one of the fastest growing industries, assuming a central role in the economy of many countries. Over the past years, new tourism products have been launched and existent ones have been adapted, such as rural tourism. The motivations for the demand of these services are aimed at revitalizing physical and psychic balance, under stress caused by modern lifestyles. The importance of rural tourism has been stressed in several studies. For instance, according to Dong, Wang, Morais and Brooks (2013) rural tourism has been frequently mentioned as an alternative form of economic development in rural areas. Other studies have emphasized that it significantly contributes to the gross national product, wealth creation, employment generation (Choong-Ki, Var & Blaine, 1996; Borooah, 1999) and to regional development (Dredge, 1999). In a more recent study, rural tourism is considered as a diversification strategy that serves as a catalyst for economic growth in remote communities (Rid, Ezeuduji & Pröbst-Haider, 2014). In the Portuguese case, there is a low profitability of rural tourism and, therefore, it is crucial to identify market segments to create appropriate marketing strategies in order to increase the profitability of rural tourism (Kastenholz, 2002). Despite the importance of better understanding what motivates tourists to choose rural tourism, studies focusing on rural tourism in Portugal have been limited (e.g. Kastenholz, Davis & Paul, 1999; Kastenholz, 2005; Almeida, Correia & Pimpão, 2014). Thus, the main aim of this study is to examine Portuguese tourists’ preferences when choosing rural tourism accommodation. The findings are crucial to support marketing strategies and for rural tourism development in Portugal. This study begins with a literature review of earlier studies concerning rural tourism, followed by the research methodology. In the fourth part, the results are discussed and finally, in the conclusions, some strategies are suggested as well as limitations of the study are presented.